Comparative Study of Effectiveness Pronatalist Policies in South Korea, Japan, Taiwan, and Singapore 2015-2023 - Mahira Sandria Rahmatiana; Adhi Cahya Fahadayna (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This study analyzed the impact of pronatalist policies on fertility rates in four Asian countries, consist of Singapore, Taiwan, South Korea, and Japan during the period 2015-2023. Following a trend previously observed in Europe, these countries experienced a significant decline in fertility along with increasing economic activity in recent years. The selected timeframe reflects a period of active implementation of pronatalist policies since 2015. This research employs a comparative quantitative approach using multiple linear regression analysis to assess the relationship between policy variables and fertility rates. Secondary data are used, based on indicators derived from Sleebos’ (2003) framework, which includes financial incentives, child care, parental leave, family-friendly workplaces, welfare state, and tax systems. The findings, linear with previous study, indicate a positive and significant relationship between several pronatalist policies and fertility rates. This study focuses on mapping the current effectiveness of these policies in countries with similiar socio-economic contexts and highlights the complex interplay between policy design and each country’s unique social, cultural, and economic conditions.